MODERN ASPECTS OF CORRECTION OF BLOOD SUGAR LEVELS IN PATIENTS WITH ACUTE HEART FAILURE WITH TYPE 2 DIABETES MELLITUS - Boltayev E. B. (Web of Journals Publishing, 2024)
Despite the studies verified by the World Health Organization on regulating the blood level in patients with acute sedentary insufficiency with type 2 diabetes mellitus, the optimal method for regulating the blood level in these patients has not been worked out. The state of research and optimization of elevated blood sugar levels in diabetic patients with acute heart failure and adequate results.
Keywords: Diabetes mellitus, acute heart failure, hyperglycemia.